2021
DOI: 10.1101/2021.06.12.448172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silkworm model forBacillus anthracisinfection and virulence determination

Abstract: Bacillus anthracis is an obligate pathogen and a causative agent of anthrax. Its major virulence factors are plasmid-coded; however, recent studies have revealed chromosome-encoded virulence factors, indicating that the current understanding of its virulence mechanism is elusive and needs further investigation. In this study, we established a silkworm (Bombyx mori) infection model of B. anthracis Sterne. We showed that silkworms were killed by B. anthracis and cured of the infection when administered with anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Pathogenic strains of B. cereus and B. anthracis have been reported to kill Bombyx and Galleria larvae (31)(32)(33)(34). It has been reported that both Bombyx and Galleria larvae harbor N. circulans in their gut under ordinary conditions (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic strains of B. cereus and B. anthracis have been reported to kill Bombyx and Galleria larvae (31)(32)(33)(34). It has been reported that both Bombyx and Galleria larvae harbor N. circulans in their gut under ordinary conditions (35,36).…”
Section: Introductionmentioning
confidence: 99%